Remodeling of the Pulmonary Circulation in Patients with Viral Liver Cirrhosis - M. V. Chistyakova; A. V. Govorin; Yu. V. Parkhomenko (Столичная издательская компания, 2019)
Aim. To study some structural and functional indicators of the right heart, as well as the effect of antiviral therapy on these parameters in patients with viral liver cirrhosis (VLC).Material and methods. Patients with VLC (n=98; mean age 40.6 years, disease duration 3.9 years) were examined. The patients were divided into 2 groups: without ascites (1 st group; n=59) and with ascites (2nd group; n=39). The control group included 22 healthy volunteers. All participants had standard and tissue Doppler echocardiography.Results. The thickness of the anterior wall of the right ventricle (RV) was increased in the 1 st and 2nd groups compared with the control (by 20% and 27%, respectively), as well as the volume index of the left atrium. The decrease in the rate of early RV filling (E) and the E/A ratio was found: in the 1st group - 0.9 [0.8;1.31 ], in the 2nd group - 0.8 [0.78; 1.2] with a control value of 1.6 [1.2;1.94] (p<0.001). Patients of the 2nd group compared with the control group and patients of the 1st group showed an increase in myocardial productivity index (by 35% and 35%, respectively) and time of isovolumetric RV filling (by 32% and 29%, respectively). RV dilatation, an increase in the index of the volume of the left atrium, dilatation of the pulmonary artery and an increase in systolic pressure in the pulmonary artery (in 2nd group - 36 [26;39] mm Hg, in 1 st group - 28 [1 9;32] mm Hg, in control - 24 [11 ;26] mm Hg; p<0.001) were also found in the 2nd group. The decrease in the maximum systolic velocity of the fibrous ring of the mitral valve in comparison with the reference level was found in 21 (36%) VLC patients with ascites and in 6 (1 6%) without ascites. The use of antiviral therapy led to a decrease in the left atrial volume index and systolic pressure in the pulmonary artery. A correlation was found between pressure level in the pulmonary artery and the Tei index (r=0.74; p<0.001), the systolic velocity of movement of the fibrous ring of the mitral valve (r=0.54; p<0.001), the diastolic velocity Em (r=0.72; p<0.001), blood flow velocity in the own liver artery (r=0.63; p<0.001) as well as the maximum systolic velocity in the portal vein (r=0.61; p<0.001).Conclusion. Structural and functional changes in the right heart and left atrium were found in VLC patients. These disorders depend on the degree of decompensation of the hepatic process and are more pronounced in patients with ascites. Antiviral therapy had a positive effect on some morpho-functional parameters of the heart. The found correlations indicate the effect of hepatic-portal blood flow on cardiohemodynamic disorders.